2010
DOI: 10.1242/jeb.046870
|View full text |Cite
|
Sign up to set email alerts
|

Differential adjustment in gill Na+/K+- and V-ATPase activities and transporter mRNA expression during osmoregulatory acclimation in the cinnamon shrimp Macrobrachium amazonicum (Decapoda, Palaemonidae)

Abstract: We evaluate osmotic and chloride (Cl(-)) regulatory capability in the diadromous shrimp Macrobrachium amazonicum, and the accompanying alterations in hemolymph osmolality and [Cl(-)], gill Na(+)/K(+)-ATPase activity, and expression of gill Na(+)/K(+)-ATPase α-subunit and V-ATPase B subunit mRNA during salinity (S) acclimation. We also characterize V-ATPase kinetics and the organization of transport-related membrane systems in the gill epithelium. Macrobrachium amazonicum strongly hyper-regulates hemolymph osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
3
49

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(141 citation statements)
references
References 71 publications
6
83
3
49
Order By: Relevance
“…While H. rubra acts as an osmoconformer at oceanic salinities (32‰), it transitions to osmoregulation at lower salinities, similar to previously studied marine euryhaline crustaceans (e.g. Zanders, 1980;Henry and Watts, 2001;Chung and Lin, 2006;Faleiros et al, 2010), including another atyid species (Born, 1968). However, 'strong' osmoregulating crustaceans with a marine ancestry such as the blue crab (Callinectes sapidus) maintain an osmotic gradient between the external medium and their hemolymph of 600 mOsm kg −1 H 2 O (Cameron, 1978;Henry, 2001).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…While H. rubra acts as an osmoconformer at oceanic salinities (32‰), it transitions to osmoregulation at lower salinities, similar to previously studied marine euryhaline crustaceans (e.g. Zanders, 1980;Henry and Watts, 2001;Chung and Lin, 2006;Faleiros et al, 2010), including another atyid species (Born, 1968). However, 'strong' osmoregulating crustaceans with a marine ancestry such as the blue crab (Callinectes sapidus) maintain an osmotic gradient between the external medium and their hemolymph of 600 mOsm kg −1 H 2 O (Cameron, 1978;Henry, 2001).…”
Section: Discussionsupporting
confidence: 52%
“…In euryhaline crustaceans, expression of these genes usually increases dramatically in the osmoregulatory gills during comparable salinity transfers (reviewed by Havird et al, 2013). For example, NKA expression in C. granulatus increased 25-to 55-fold after transfer from SW to 45‰ and 2‰ (Luquet et al, 2005), with similar results for Scylla paramamosain (Chung and Lin, 2006), Pachygrapsus marmoratus (Jayasundara et al, 2007), C. sapidus (Serrano et al, 2007), C. maenas (Serrano and Henry, 2008;Jillette et al, 2011), Macrobrachium amazonicum (Faleiros et al, 2010) and Litopenaeus vannamei (Wang et al, 2012). Although utilized in fewer studies, CAc (but not CAg) (see Serrano and Henry, 2008), NKCC, HAT and AK (e.g.…”
Section: Research Articlementioning
confidence: 78%
“…Several studies have identified specific genes involved in osmoregulation in crustacean species that include NKA, NKCC, VTA, CA and Cystic fibrosis transmembrane regulator (CFTR) (Pongsomboon et al, 2009;Faleiros et al, 2010;Havird et al, 2013). Functional roles of these genes are known to be: NKA establishes an electromechanical gradient across the gill cell membrane; NKCC transports ions into gill cells from the blood or the environment depending on salinity level; VTA pumps protons to influence HCO 3 -and Cl -exchange, and Na + uptake; CA produces H + and HCO 3 -that are needed to drive Na + and Cl -exchange; and CFTR is the Cl -channel regulator for osmoregulation in crustaceans (Singer et al, 1998;Hwang and Lee, 2007;Moshtaghi et al, 2016 (Foster et al, 2010;Havird et al, 2013;Scott and Brix, 2013).…”
Section: Crustacean Taxa In Evolutionary Studiesmentioning
confidence: 99%
“…All experimental tanks were maintained at 6‰ (a level that we considered as control salinity) for two weeks to minimize environmental impacts on gene expression and body physiology (hemolymph). Previous investigations have shown that crustaceans can acclimate well to different salinity conditions within 1-3 days depending on the relative salinity stress level (Lovett et al, 2006;Roy et al, 2007;Charmantier et al, 2009;Faleiros et al, 2010;Havird et al, 2014). While this strategy may not rule out all environmental effects completely, we consider that it will provide a robust foundation for assessing the impact of salinity level on experimental individuals.…”
Section: Specimen Collection and Transportmentioning
confidence: 99%
See 1 more Smart Citation